Crystal structure of 5,15-dihexyl-5,15-dihydrobenzo[2,1-b:4,3-c′]dicarbazole hexane 0.375-solvate - Dingchao Zhang; Longqiang Shi; Zhi Liu; Li Li; Zhenhao Hu; Deliang Cui; Jing Yang (Acta Crystallographica Section E: Crystallographic Communications, 2018)
The title compound, C38H40N2·0.375C6H14, crystallizes in the monoclinic space group P21/c and has a host–guest structure with the helicene molecules forming a porous structure and molecules of hexane inserted into the holes. The dihedral angles between the two carbazole sections of the right- and left-handed helicenes are 27.44 (3) and 25.63 (3)°, respectively. There are no classical π–π interactions or hydrogen-bonding interactions present between adjacent molecules in the crystal structure. The hexane solvent molecule shows positional disorder.